10z-22=3(3z+11)-z

Simple and best practice solution for 10z-22=3(3z+11)-z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10z-22=3(3z+11)-z equation:



10z-22=3(3z+11)-z
We move all terms to the left:
10z-22-(3(3z+11)-z)=0
We calculate terms in parentheses: -(3(3z+11)-z), so:
3(3z+11)-z
We add all the numbers together, and all the variables
-1z+3(3z+11)
We multiply parentheses
-1z+9z+33
We add all the numbers together, and all the variables
8z+33
Back to the equation:
-(8z+33)
We get rid of parentheses
10z-8z-33-22=0
We add all the numbers together, and all the variables
2z-55=0
We move all terms containing z to the left, all other terms to the right
2z=55
z=55/2
z=27+1/2

See similar equations:

| (14x-94)+78=102 | | 3x=2x+4=5x−8 | | -6x-2x=3x | | 25x7=0 | | 38-8m=-6(-7m+2) | | 8x+37+12x+23=360 | | 3k(2k+7)=15 | | 5x+28=-2 | | 8x+37+12x+23=90 | | -7x+16-3x-4=72 | | 4(2+3x)=40 | | 8x+37+12+23=180 | | 17^2x=17^3x-8 | | 16=3x+x | | 6x-14x=16=-35+11 | | 1.29(x+4)=7.20 | | 17^2x=16^3x-8 | | 1/8=1/(2(x+9)^1/2) | | 8x+37=12+23 | | 5x+5x-2=28 | | 17/20=tT9-(13/20) | | 3=3x^2+2+6x | | -4x+3=5x-12 | | (2p-7)(4p+3)=3 | | 2x+6x+3=27 | | 0.05(n-520)=106 | | 2v-7(-3v-7)=-31+7v | | 3x+7=-9-5x | | Y=4+5xX=5 | | -1+m/2=-4 | | 3x-3((12-2x)/3)=3 | | 10-5m=14+7m |

Equations solver categories